A method for the preparation of a multi-stage co-precipitated iron-based fischer-tropsch synthesis catalyst
Patent Information
- Application Number
- CN202611204717.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-10
- Publication Date
- 2026-10-30
AI Technical Summary
[0007]综上所述,现有技术仍存在以下技术瓶颈:在组分设计方面,缺乏多种金属协同效应的系统性设计,轻烃选择性低,副产物
和
选择性较高;在制备工艺方面,普遍使用碳酸钠引入钠离子杂质,碱金属助剂分布不均匀,且沉淀、焙烧、还原各工序相对孤立,缺乏针对活性相演变规律的关联性设计;在反应器适配性方面,绝大多数技术方案仅单一针对浆态床或固定床
[0032]本发明通过引入镧和镍双金属助剂并精确控制其比例,产生了单一金属助剂所不具备的协同催化效应,结合多段共沉淀、梯度焙烧与梯度还原在活性相演变不同阶段的精准匹配,实现了对产物碳数分布的超常规调控。
Smart Images

Figure SMS_198
Abstract
Description
Technical Field
[0001] This invention belongs to the field of Fischer-Tropsch synthesis catalyst technology, specifically relating to a method for preparing a multi-stage co-precipitation iron-based Fischer-Tropsch synthesis catalyst. Background Technology
[0002] my country's dependence on imported oil has long been high, and its transportation routes are limited, posing potential supply risks. To ensure national energy security, it is urgent to develop non-oil-based liquid fuel production technologies. This includes producing syngas via routes such as indirect coal liquefaction, natural gas conversion, and biomass utilization, followed by Fischer-Tropsch synthesis. Liquid light hydrocarbons can bypass the oil route and achieve diversified energy supply, which is of great strategic significance for alleviating the contradiction between domestic oil supply and demand and reducing dependence on foreign oil.
[0003] Fischer-Tropsch synthesis refers to the synthesis of syngas In the reaction process of converting into hydrocarbon compounds under the action of a catalyst, iron-based catalysts with iron as the active component are among the most widely used Fischer-Tropsch synthesis catalysts in industrial applications due to their advantages such as low price, moderate activity of water-gas shift reaction, and adjustable product distribution.
[0004] However, existing iron-based Fischer-Tropsch synthesis catalysts still face core technological bottlenecks in industrial applications: the products exhibit a wide carbon number distribution, which is problematic for... High-selectivity production of light hydrocarbon fractions is particularly difficult; meanwhile, iron-based catalysts readily generate large amounts of [unspecified substances] in water-gas shift reactions. The byproducts, methanation side reactions are also quite serious, resulting in low carbon atom utilization efficiency, which restricts the economic efficiency and carbon emission reduction benefits of the process.
[0005] To improve the performance of iron-based catalysts, major domestic research institutions and enterprises have conducted extensive research in the field of Fischer-Tropsch synthesis catalysts. Chinese invention patent CN1260007C discloses a microspherical iron-based catalyst for Fischer-Tropsch synthesis, its preparation method, and its application. This catalyst... As a composition, sodium carbonate is used as a precipitant, and the product contains... Selectivity is lower than , Selectivity is higher However, this patent uses sodium carbonate as a precipitant to introduce sodium ion impurities, requiring repeated washing with large amounts of deionized water, and the added cerium salt is expensive. There is insufficient targeted optimization for light fractions. The above-mentioned heavy hydrocarbons account for a relatively high proportion.
[0006] Chinese invention patent CN103071501A discloses an iron-based catalyst for Fischer-Tropsch synthesis and its preparation method, employing a metal powder oxidation ball milling route. However, this method suffers from low dispersion of the active component and severely insufficient control over the selectivity for light hydrocarbons. Chinese invention patent CN101767010B discloses a highly wear-resistant iron-based catalyst for use in slurry bed reactors, specifically targeting… High selectivity of heavy hydrocarbon production Light hydrocarbons have extremely low selectivity, and the introduction of boron increases environmental risks.
[0007] In summary, existing technologies still suffer from the following bottlenecks: Regarding component design, there is a lack of systematic design for synergistic effects of multiple metals. Light hydrocarbons have low selectivity and produce byproducts. and The selectivity is relatively high; in terms of preparation process, sodium carbonate is generally used to introduce sodium ion impurities, the distribution of alkali metal additives is uneven, and the precipitation, calcination and reduction processes are relatively isolated, lacking a correlation design for the evolution law of the active phase; in terms of reactor adaptability, most technical solutions are only designed for slurry beds or fixed beds. Summary of the Invention
[0008] To address the technical problems existing in the prior art, this invention discloses a method for selective production of Fischer-Tropsch synthesis reaction. The present invention discloses an iron-based catalyst containing lanthanum-nickel bimetallic additives for light hydrocarbon fractions, and also discloses a multi-stage co-precipitation method for preparing the iron-based catalyst.
[0009] To achieve the above objectives, the technical solution adopted in this invention is as follows: a method for preparing a multi-stage co-precipitation iron-based Fischer-Tropsch synthesis catalyst, the specific steps of which are as follows:
[0010] Step 1: Dissolve iron, copper, and manganese salts in deionized water, and add at least one metal salt, such as lanthanum or nickel, to prepare a solution with a total metal ion concentration of [missing value]. A mixed salt solution, wherein the amount of metal salt added is expressed as a percentage of the mass of iron. ;
[0011] Step 2: Dissolve potassium carbonate in deionized water to prepare a solution with a concentration of [missing information]. Potassium carbonate solution was used as a precipitant;
[0012] Step 3: Add the mixed salt solution from Step 1 and the potassium carbonate solution from Step 2 into the reactor in parallel flow, and use a multi-stage temperature control method for co-precipitation;
[0013] Step 4: Place the precipitated slurry obtained in Step 3 in... Below, aging Solid-liquid separation was then performed, and the filter cake was washed with deionized water until the potassium ion content in the washing liquid was below [a certain level]. A solid precipitate was obtained;
[0014] Step 5: Re-pulverize the solid precipitate obtained in Step 4, add potassium salt solution and silica sol, mix thoroughly, and add or not add at least one metal salt from lanthanum or nickel salt, the amount of which is calculated as a percentage of the mass of iron. This forms a catalyst slurry with a solid content of [missing information]. ;
[0015] Step Six: Spray dry the catalyst slurry obtained in Step Five. The inlet air temperature for spray drying is... The outlet air temperature is To obtain the particle size The microspherical powder is then subjected to staged gradient calcination in air atmosphere to obtain the catalyst precursor.
[0016] Step 7: The catalyst precursor obtained in Step 6 is subjected to gradient reduction and activation in a tubular fixed-bed reactor or a slurry-bed reactor to obtain the iron-based catalyst product.
[0017] In step one, the iron salt is at least one of ferric nitrate, ferric sulfate, or ferric chloride, preferably ferric nitrate;
[0018] The copper salt is at least one of copper nitrate, copper sulfate, or copper chloride, with copper nitrate being preferred;
[0019] The manganese salt is at least one of manganese nitrate, manganese sulfate, or manganese chloride, with manganese nitrate being preferred;
[0020] The metal salt is lanthanum nitrate. , nickel nitrate At least one of them, preferably containing both lanthanum nitrate and nickel nitrate.
[0021] When the added metal salt contains both lanthanum and nickel, the weight ratio of La to Ni is: .
[0022] In step two, the amount of potassium carbonate used is: [calculated as] the total number of moles of metal ions in the mixed salt solution, based on the number of moles of carbonate provided by potassium carbonate. times.
[0023] In step three, the reaction temperature is controlled in two stages: a low-temperature stage and a high-temperature stage.
[0024] Temperature control in the low-temperature range The pH value in the low-temperature range is controlled at The continuous feeding time accounts for the total feeding time. ;
[0025] Temperature control in the high-temperature section The pH value in the high-temperature range is controlled at Complete the remaining feeding.
[0026] In step five, the potassium salt is at least one of potassium carbonate, potassium nitrate, or potassium silicate; the silica sol... Content is The particle size is ;
[0027] The amount of metal salt added during the pulping stage is consistent with the type of metal salt selected in step one, forming a dual gradient distribution of metal in the catalyst, namely "bulk phase-surface".
[0028] In step six, the conditions for staged gradient calcination are: The rate of temperature increase from room temperature to Constant temperature insulation , and then The heating rate increased to Constant temperature insulation The catalyst precursor was obtained.
[0029] In step seven, the specific steps of gradient reduction activation are as follows: under an inert atmosphere... Heat up to Switch to hydrogen volume content Reducing gas, constant temperature reduction ; and then Heat up to Increase the hydrogen volume content to isothermal reduction The reduction pressure is The activated iron-based catalyst product was obtained.
[0030] After gradient reduction activation, add an in-situ oxidation-carbonization activation step: lower the temperature to... The volume fraction of the substance is . Selective oxidation treatment of inert gases The temperature then rose to Switch to molar ratio is The synthesis gas is carbonized. .
[0031] This invention provides a method for preparing a precipitated iron-based Fischer-Tropsch synthesis catalyst, which utilizes lanthanum-nickel bimetallic synergy, manganese promoter chain growth inhibition, and bulk phase... Multiple mechanisms, including surface-based dual-gradient metal distribution and in-situ activation via oxidation-carbonization, effectively regulate the distribution of Fischer-Tropsch synthesis products, concentrating the products in... Light fraction; utilizing manganese and copper synergistic inhibition of methanation, potassium auxiliary agent to regulate surface alkalinity, and lanthanum stabilization. The active phase and gradient reduction optimize the composition of the active phase, significantly suppressing side reactions and reducing the generation of methane and carbon dioxide. Through processes such as spray drying, silica sol enhancement, and gradient calcination reduction, the catalyst has a low wear index and high mechanical strength, making it suitable for both tubular fixed-bed reactors and slurry-bed reactors.
[0032] This invention introduces lanthanum and nickel bimetallic additives and precisely controls their ratio to produce a synergistic catalytic effect that single metal additives cannot achieve. By combining multi-stage co-precipitation, gradient calcination and gradient reduction at different stages of active phase evolution, the invention achieves unconventional control over the carbon number distribution of the product. Detailed Implementation
[0033] To make the technical problems, technical solutions, and beneficial effects of this invention clearer, the invention will be further described in detail below with reference to embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.
[0034] Example 1
[0035] Step 1: Take ferric nitrate Copper nitrate manganese nitrate Lanthanum nitrate , nickel nitrate Dissolved in deionized water, the solution was prepared with a total metal ion concentration of approximately A mixed salt solution.
[0036] Step 2: Add potassium carbonate Dissolve in deionized water to prepare approximately A potassium carbonate solution.
[0037] Step 3: Add deionized water to the reaction vessel and preheat to [temperature]. Under stirring at 300 rpm, the mixed salt solution and potassium carbonate solution were added to the reactor at a constant rate for co-precipitation in a low-temperature section. The value was 7.5, the feeding time was 30 minutes, and the reaction temperature was maintained at 7.5. Then, the temperature of the reactor is gradually increased to [temperature value] over 20 minutes. ,adjust The value was increased to 8.0, and the remaining 30 minutes of feeding were completed. The reaction temperature in the high-temperature section was controlled at [value missing]. .
[0038] Step 4: After adding the ingredients, Continue stirring and aging for 90 minutes. After aging, perform vacuum filtration and repeatedly wash the filter cake with deionized water until the potassium ion content in the washing liquid is below [value missing]. .
[0039] Step 5: Transfer the washed filter cake back to the pulping kettle, add deionized water to form a flowing slurry, and add lanthanum nitrate, nickel nitrate, potassium nitrate, and... Content is The silica sol was thoroughly stirred for 60 minutes until homogeneous, and the solid content of the slurry was controlled to be approximately [missing information]. .
[0040] Step 6: Spray dry the slurry and set the inlet air temperature. Air outlet temperature The particle size was found to be mainly distributed in The resulting microspherical powder was placed in a muffle furnace and then... Heat up to Keep warm for 2 hours, then... Heat up to Keep warm for 3 hours, then let cool naturally.
[0041] Step 7: Load the catalyst precursor into a tubular fixed-bed reactor, and purge with nitrogen for 30 minutes; Heat up to Switch to Mixed gas ( Volume content ), constant temperature reduction for 1 hour; then with Heat up to Switch to pure hydrogen gas, reduce at a constant temperature for 4 hours, and reduce at atmospheric pressure.
[0042] through The weight ratio of each component of the catalyst was determined as follows:
[0043] .
[0044] Example 2
[0045] The catalyst was prepared according to the method of Example 1, with the difference that: in step one, nickel nitrate was not added, only lanthanum nitrate was added; in step five, lanthanum nitrate was added, but nickel nitrate was not added; the final catalyst composition was:
[0046] .
[0047] Example 3
[0048] The catalyst was prepared according to the method in Example 1, except that lanthanum nitrate was not added in step one, only nickel nitrate was added. In step five, nickel nitrate is added. Lanthanum nitrate is not added; the final catalyst composition is .
[0049] Example 4
[0050] The catalyst was prepared according to the method in Example 1, except that an oxidation-carbonization in-situ activation step was added after the gradient reduction activation in step seven: the temperature was lowered to [temperature missing] in a hydrogen atmosphere. Switch to Volume content Selective oxidation with nitrogen gas was performed for 15 minutes; then the temperature was increased to... Switch to Syngas with a molar ratio of 1.5 was carbonized for 2 hours.
[0051] Example 5
[0052] The catalyst was prepared according to the method in Example 1, the difference being the adjustment of the process parameters for multi-stage temperature-controlled co-precipitation: the temperature of the low-temperature stage... , Value control at Feeding time: 20 minutes; High temperature zone temperature The pH value was controlled at 8.3, and the feeding time was 40 minutes.
[0053] Example 6
[0054] The catalyst was prepared according to the method in Example 1, the difference being the adjustment of the amount of lanthanum and nickel added. Lanthanum nitrate and nickel nitrate were added in both step one and step five. The final catalyst composition was as follows:
[0055] , weight ratio .
[0056] Example 7
[0057] The catalyst was prepared according to the method in Example 1, except that the catalyst was evaluated in a slurry bed reactor. The activated catalyst was added to a high-pressure stirred tank slurry bed reactor with an inner diameter of 50 mm, using liquid paraffin as the liquid phase medium. The solid content of the catalyst in the liquid phase was approximately... reaction temperature Reaction pressure ,airspeed The stirring speed is 600 rpm.
[0058] Example 8
[0059] The catalyst was prepared according to the method of Example 1, except that the amount of silica sol added in step five was adjusted, and the final catalyst composition was as follows:
[0060] .
[0061] Example 9
[0062] The catalyst was prepared according to the method in Example 1, except that the amount of copper nitrate added in step 1 was adjusted. The final catalyst composition was as follows:
[0063] .
[0064] Example 10
[0065] The catalyst was prepared according to the method in Example 1, except for the adjustment of the gradient reduction activation parameters in step seven: under an inert atmosphere... Heat up to Switch to Volume content The reducing gas was used for reduction at a constant temperature for 1.5 hours; then... Heat up to Switch to pure hydrogen and reduce at a constant temperature for 5 hours.
[0066] Example 11
[0067] The catalyst was prepared according to the method in Example 1, except that in step one: lanthanum nitrate and nickel nitrate were added simultaneously. , mass ratio The total amount of rare earth added is the mass of Fe. Total metal ion concentration in mixed salts .
[0068] Step 2: Potassium carbonate precipitant Molar amount of carbonate The total molar amount of metal is 1.0 times.
[0069] Step 3: Low-temperature section feed accounts for a portion of the total feed. Low temperature , ;high temperature , .
[0070] Step 5: Supplement The total amount added is Fe mass ;Slurry solids content Silica sol Colloidal particles 10nm.
[0071] Step Six: First-Stage Heating , Maintain temperature for 1 hour; second-stage heating , Keep at a constant temperature for 2 hours.
[0072] Step 7: Restore the first order , constant temperature Second order , Maintain temperature for 2 hours; reduction pressure Carbonization Carbonization for 1 hour; oxidation Oxidize for 5 minutes.
[0073] Final composition: ; .
[0074] Example 12
[0075] The catalyst was prepared according to the method in Example 1, except for step one: mass ratio The total amount of rare earth added is the mass of Fe. Total metal ion concentration in mixed salts .
[0076] Step 2: Potassium carbonate Molar amount of carbonate ions = total molar amount of metal ions times.
[0077] Step 3: Low-temperature section feed accounts for a portion of the total feed. Low temperature , ;high temperature , .
[0078] Step 5: Supplement The total amount added is Fe mass ;Slurry solids content Silica sol Colloidal particles 30nm.
[0079] Step Six: First-Stage Heating , Maintain temperature for 3 hours; second-stage heating , Keep at a constant temperature for 5 hours.
[0080] Step 7: Restore the first order , Constant temperature for 2 hours; second stage , Constant temperature for 6 hours; reduction pressure Carbonization Carbonization for 4 hours; oxidation Oxidize for 30 minutes.
[0081] Final composition:
[0082] ;
[0083] .
[0084] Example 13
[0085] The catalyst was prepared according to the method in Example 1, the difference being the in-situ activation and carbonization. The molar ratio is 1.0.
[0086] Example 14
[0087] The catalyst was prepared according to the method in Example 1, the difference being the in-situ activation and carbonization. The molar ratio is 2.0.
[0088] Example 15
[0089] The catalyst was prepared according to the method in Example 1, except that the silica sol was... Colloidal particles 10nm.
[0090] Example 16
[0091] The catalyst was prepared according to the method in Example 1, except that the silica sol was... Colloidal particles 30nm.
[0092] Example 17
[0093] The catalyst was prepared according to the method of Example 1, except that Example 4 included oxidative carbonization activation, and the reduction pressure was changed to 0.1 MPa.
[0094] Example 18
[0095] The catalyst was prepared according to the method of Example 1, except that Example 4 included oxidative carbonization activation, and the reduction pressure was changed to 1.0 MPa.
[0096] Example 19
[0097] The catalyst was prepared according to the method of Example 1, except that no La or Ni salts were added in steps one and five, while the remaining process parameters were the same as in Example 1; Composition:
[0098] No rare earth / nickel additives.
[0099] Example 20
[0100] The catalyst was prepared according to the method of Example 1, except that the precipitant was replaced with an equimolar amount of sodium carbonate.
[0101] Catalyst evaluation method: Fixed-bed reactor evaluation (except for Example 7): The activated catalyst was loaded into a tubular fixed-bed reactor with an inner diameter of 12 mm, and the bed was filled with quartz sand on both the top and bottom. The reaction feed gas was... Syngas with a molar ratio of 1.5 was used, and the total gas flow rate was precisely controlled by a mass flow meter. The volumetric hourly space velocity (GHSV) was set according to each embodiment. The reaction temperature and pressure were set according to each embodiment. After gas-liquid separation, the gas phase product was analyzed online using an Agilent 7890B gas chromatograph, and the liquid phase product was analyzed using a gas chromatography-mass spectrometry (GC-MS) system. Carbon number distribution analysis was performed. CO conversion and product selectivity were calculated based on carbon atom balance.
[0102] Evaluation of slurry bed reactor (Example 7): An activated catalyst was added to a high-pressure stirred tank slurry bed reactor with an inner diameter of 50 mm. Liquid paraffin was used as the liquid phase medium, and the solid content of the catalyst in the liquid phase was approximately... The reaction feed gas is Syngas with a molar ratio of 1.5, reaction temperature The reaction pressure was 2.5 MPa and the space velocity was... The stirring speed is 600 rpm.
[0103] The catalyst evaluation results are listed in Table 1.
[0104] Table 1. Evaluation results of catalytic performance of the examples in the Fischer-Tropsch synthesis reaction
[0105]
[0106] The above are merely preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the scope of the present invention.
Claims
1. A method for preparing a multi-stage co-precipitation iron-based Fischer-Tropsch synthesis catalyst, characterized in that, The specific steps are as follows: Step 1: Dissolve iron, copper, and manganese salts in deionized water, and add at least one metal salt, such as lanthanum or nickel, to prepare a solution with a total metal ion concentration of [missing value]. A mixed salt solution, wherein the amount of metal salt added is calculated as the mass of iron element. ; Step 2: Dissolve potassium carbonate in deionized water to prepare a solution with a concentration of [missing information]. Potassium carbonate solution was used as a precipitant; Step 3: Add the mixed salt solution from Step 1 and the potassium carbonate solution from Step 2 into the reactor in parallel flow, and use a multi-stage temperature control method for co-precipitation; Step 4: Place the precipitated slurry obtained in Step 3 in... Below, aging Solid-liquid separation was then performed, and the filter cake was washed with deionized water until the potassium ion content in the washing liquid was below [a certain level]. A solid precipitate was obtained; Step 5: Re-pulverize the solid precipitate obtained in Step 4, add potassium salt solution and silica sol, mix thoroughly, and add or not add at least one metal salt from lanthanum or nickel salt, wherein the amount added is calculated as a percentage of the mass of iron. This forms a catalyst slurry with a solid content of [missing information]. ; Step Six: Spray dry the catalyst slurry obtained in Step Five. The inlet air temperature for spray drying is... The outlet air temperature is To obtain the particle size The microspherical powder is then subjected to staged gradient calcination in air atmosphere to obtain the catalyst precursor. Step 7: The catalyst precursor obtained in Step 6 is subjected to gradient reduction activation in a tubular fixed-bed reactor or a slurry-bed reactor to obtain the iron-based catalyst product.
2. The method for preparing a multi-stage co-precipitation iron-based Fischer-Tropsch synthesis catalyst according to claim 1, characterized in that, In step one, the iron salt is at least one of ferric nitrate, ferric sulfate, or ferric chloride; The copper salt is at least one of copper nitrate, copper sulfate, or copper chloride; The manganese salt is at least one of manganese nitrate, manganese sulfate, or manganese chloride; The metal salt is lanthanum nitrate. , nickel nitrate At least one of them.
3. The method for preparing a multi-stage co-precipitation iron-based Fischer-Tropsch synthesis catalyst according to claim 2, characterized in that, When the added metal salt contains both lanthanum and nickel, the weight ratio of La to Ni is: .
4. The method for preparing a multi-stage co-precipitation iron-based Fischer-Tropsch synthesis catalyst according to claim 3, characterized in that, In step two, the amount of potassium carbonate used is: [calculated as] the total number of moles of metal ions in the mixed salt solution, based on the number of moles of carbonate provided by potassium carbonate. times.
5. The method for preparing a multi-stage co-precipitation iron-based Fischer-Tropsch synthesis catalyst according to claim 4, characterized in that, In step three, the reaction temperature is controlled in two stages: a low-temperature stage and a high-temperature stage. Temperature control in the low-temperature range The pH value in the low-temperature range is controlled at The continuous feeding time accounts for the total feeding time. ; Temperature control in the high-temperature section The pH value in the high-temperature range is controlled at Complete the remaining feeding.
6. The method for preparing a multi-stage co-precipitation iron-based Fischer-Tropsch synthesis catalyst according to claim 5, characterized in that, In step five, the potassium salt is at least one of potassium carbonate, potassium nitrate, or potassium silicate; the silica sol... Content is The particle size is ; The amount of metal salt added during the pulping stage is the same as the type of metal salt selected in step one.
7. The method for preparing a multi-stage co-precipitation iron-based Fischer-Tropsch synthesis catalyst according to claim 6, characterized in that, In step six, the conditions for staged gradient calcination are: The rate of temperature increase from room temperature to Constant temperature insulation , and then The heating rate increased to Constant temperature insulation The catalyst precursor was obtained.
8. The method for preparing a multi-stage co-precipitation iron-based Fischer-Tropsch synthesis catalyst according to claim 7, characterized in that, In step seven, the specific steps of gradient reduction activation are as follows: under an inert atmosphere... Heat up to Switch to hydrogen volume content Reducing gas, constant temperature reduction ; and then Heat up to Increase the hydrogen volume content to constant temperature reduction The reduction pressure is The activated iron-based catalyst product was obtained.
9. The method for preparing a multi-stage co-precipitation iron-based Fischer-Tropsch synthesis catalyst according to claim 8, characterized in that, In step seven, after the gradient reduction activation is completed, an oxidation-carbonization in-situ activation step is added: the temperature is reduced to... The volume fraction of the substance is 100%. Selective oxidation treatment of inert gases The temperature then rose to Switch to molar ratio is The synthesis gas is carbonized. .
Citation Information
Patent Citations
High-resistance wear-resistant ferrum-based catalyst used in slurry bed reactor and preparation method thereof
CN101767010B
Iron-based catalyst for Fischer-Tropsch synthesis and preparation method thereof
CN103071501A
Micro-ball iron-based catalyst for Fischer-Tropsch synthesis and its preparation and use
CN1260007C
